Management quality and acquisition performance: New evidence based on firm profitability. Issue 3 (8th July 2019) - Liu, Qingfeng; Sono, Hui; Zhang, Wei
Abstract: Using corporate accounting profitability measures to proxy for management quality, we report evidence that acquisitions made by higher quality acquirers create greater shareholder value. More profitable acquirers earn better stock returns over the long term, although no consistent relationship is found between announcement‐period abnormal returns and firm profitability. More profitable acquirers also preserve shareholder value by reducing the likelihood of paying stock for acquisitions or overpaying the targets. Overall, our results provide new support for the hypothesis that better acquirers make better acquisitions. Our results also convey a clear message to corporate accounting and financial executives, outside investors, and other professionals. When firms with poor accounting profitability make acquisitions, it is usually not good news.